Transformation of Digital Animation Videos in Islamic Religious Education Learning to Improve Students' Understanding at MI Az-Zainiyah II - Moh Ulum; Umi Kulsum (Indonesian Journal of Education Research (IJoER), 2026)
Purpose of the study: This study aims to analyze how Islamic Religious Education (IRE) learning has undergone a transformation in the digital era through the use of digital animated videos and its implications for student understanding at MI Az-Zainiyah II. The background of this research begins with digitalization, which encourages IRE teachers to utilize technology to improve the quality of learning processes and outcomes, in line with the Independent Curriculum. Methodology: This study uses a qualitative approach with a case study approach. Data were collected in the odd semester of 2025/2026 through participant observation, interviews with three key informants (the principal, curriculum department, and fiqh teacher) and students, documentation of teaching materials, and a literature review. Data validity was strengthened through triangulation of sources and techniques, as well as member checking with informants. Analysis was conducted through data reduction, presentation, and drawing conclusions. Main Findings: The research results show that this transformation is perceived positively because digital media innovations create engaging learning environments, reduce boredom, enrich interactions, and encourage imagination and practice. However, negative impacts were also identified, including the risk of assessment inaccuracy when devices are used in semester exams and a tendency for students to be reluctant to write. Therefore, madrasas are implementing digital adoption selectively and gradually. Novelty/Originality of this study: The novelty of this research lies in its analysis of the transformation of Islamic Religious Education (IRE) learning through digital animated videos based on constructivism and dual coding theory, which emphasizes active student involvement in constructing understanding. This research focuses not only on media effectiveness but also on institutional readiness, infrastructure limitations, and teacher competency in the context of elementary madrasahs.